Pengurusan Sisa Elektrik dan Elektronik (E-Sisa) dalam Kalangan Isi Rumah: Kajian Kes Wilayah Persekutuan Labuan: Waste Electrical and Electronic Equipment (E-waste)) Management among Households: Case Study in Federal Territory of Labuan - George, Fionna; Mapa, Mohammad Tahir; Sunsearry Potirik, Ernita Eva; Dinggai, Molia Sebi Anak (GEOGRAFI, 2018)
This article relates to e-waste management scenarios in the Federal Territory of Labuan where the focus is on the management of e-waste from households. Systematic e-waste management should include e-waste management from industry and household. However, in Malaysia, e-waste management generated from household is not well managed which has a negative impact on the environment and humans. This study has two objectives, namely identifying household behavior and assessing the level of household knowledge about e-waste. This study uses questionnaires as the main instrument given to 100 respondents consisting of households. Descriptive analysis such as frequency and crosstabs were used to analyze the study data to answer the objective of the study. The results show that there are many reasons for the replacement of electronic equipment by respondents. In addition, respondents also prefer to dispose of used electronic equipment along with domestic waste compared to other means such as television (28%), computer (13%), laptop (15%), cellphone (27%), washing machine 25%), oven (17%) and air conditioning (15%) that have been thrown into the trash. The findings also show that e-waste knowledge amongst respondents is still low. Therefore, it is hoped that this study will highlight the e-waste management scenario of households in the Federal Territory of Labuan.